TRANSFORMASI DIGITAL MELALUI TEKNOLOGI INFORMASI: ADAPTASI PERAN GURU PEREMPUAN SEKOLAH DASAR PADA MASA PANDEMI - Imelda Wahyuni (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2022)
The intensity and existence of information technology underwent an instant transformation during the Covid-19 pandemic, including the education line. This paper reveals the existence of information technology as a medium for adapting the role of women in primary school education. Using qualitative research methods with a case study approach and gender shows that, first, the implementation of online learning managed by female teachers at Elementary Schools in Kendari City is supported by information technology to balance two things; ability and possibility. Female teachers have the same opportunity to show roles without cultural and structural restrictions. Second, mentoring children in online education carried out by women as mothers (educating figures in the family) and extending the function of teachers in schools (extra-burden) as a result of providing education based on government regulations (study from home) during the COVID-19 pandemic. Information technology makes it easy to publicize gaps that reduce the content and quality of female educators due to the extra burden they carry. Third, online public education services carried out by female teachers through digital media in various forms (tutorials, lectures, and publications of scientific works), which can be seen in the learning process. This study is expected to have implications for the balance and suitability of government policies related to digital transformation through information technology in the world of education to maximize the role of women in public and domestic spaces during the Covid-19 pandemic.